Social Media Usage and the Academic Engagement of Junior High School Students in Northwestern Ghana - Puobanye, Christiana; Siita, Niamatu; Seidu, Emelia (Journal of Social and Scientific Education, 2026)
Despite the growing prevalence of social media among adolescents, limited research has examined its direct impact on academic engagement among Junior High School (JHS) students in underserved contexts. While prior studies have explored social media’s effects on academic performance, procrastination, and peer interaction, few have investigated how students’ digital behaviours influence engagement in learning activities, highlighting an important empirical gap. This study argues that social media exerts a dual influence, simultaneously enabling learning through collaboration and access to educational resources, while also fostering distraction and superficial learning. Guided by the research question, "How do social media use patterns and contextual factors shape the academic engagement of JHS students in the Wa Municipality?" the study adopted a qualitative approach. Data were collected through focus group discussions and semi-structured interviews with purposively sampled students, teachers, and parents. Thematic content analysis generated axial codes, subthemes, and main themes, including levels of social media use, academic benefits and disruptions, and regulatory gaps. Findings reveal that social media both supports learning and undermines attention and self-regulation. The study underscores the need for structured digital literacy programs, proactive adult mediation, and school-based policies to balance social media use. These insights contribute to understanding the nuanced role of social media in adolescent educational engagement and inform strategies for responsible digital integration in schools.